2022
DOI: 10.14444/8210
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the Lumbar Facet Joint After Full Endoscopic Resection for Lumbar Osteoid Osteoma: Case Report and Literature Review

Abstract: Background: Osteoid osteoma (OO) is a common benign bone tumor; however, approximately 25% of cases have spine involvement. It is often treated by image-guided radiofrequency ablation to break down the nidus. Few reports have described full endoscopic resection of the lesion, but none have described postoperative remodeling of the lumbar facet joint after surgical resection of an OO. The study aimed to describe a rare case of remodeling of the lumbar facet joint and then delineate the least invasive surgical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Using endoscopic surgery for spinal OO excision has been shown to minimise the associated morbidity when compared with other surgical techniques. Following an exhaustive literature search focused on studies detailing endoscopic excision of OO, we identified nine relevant studies18–26 (table 1). The collective findings from these studies, spanning the cervical, thoracic and lumbar spine, consistently showcase successful outcomes accompanied by minimal complication rates (table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Using endoscopic surgery for spinal OO excision has been shown to minimise the associated morbidity when compared with other surgical techniques. Following an exhaustive literature search focused on studies detailing endoscopic excision of OO, we identified nine relevant studies18–26 (table 1). The collective findings from these studies, spanning the cervical, thoracic and lumbar spine, consistently showcase successful outcomes accompanied by minimal complication rates (table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Xie et al reported 11 cases of symptomatic benign spinal lesions of the lumbar and sacral spine treated with full spinal endoscopy, and all patients showed symptomatic relief with no recurrence during 1-3 years of follow-up [17]. In 2022, Kotheeranurak et al reported treatment of a case of osteoid osteoma of the L3 vertebral body with no recurrence at 2 years follow-up [18].…”
Section: Discussionmentioning
confidence: 99%
“…Hikata et al reported a case of cervical spinal OO treated with microendoscopic resection and demonstrated remodeling in the resected site at one year postoperative CT [ 17 ]. Kotheeranurak et al presented a lumbar spinal OO treated with endoscopic resection, showing remodeling of the lumbar facet joint at two years postoperative CT [ 18 ]. These suggested that bone remodeling can be expected within one to two years after endoscopic and microscopic, less invasive surgery of the spinal OO.…”
Section: Discussionmentioning
confidence: 99%